Hubungan Antara Tayangan Iklan dalam Sinetron Anak Langit dengan Pengetahuan Siswa-Siswi SMKN 2 Karawang terhadap Produk Pop Mie Pedes Dower - P., Ana Fitriana; Rosyada, Atika (Jurnal Politikom Indonesiana, 2018)
This study aims to determine the relationship between Ads Impressions in cinema Anak Langit with Knowledge of Vocational High School 2 Karawang Students towards Pop Mie Pedes Dower Product. This research uses Quantitative method. Respondents in this study were the students of Vocational High School 2 Karawang. Data collection techniques used in this study using questionnaires / questionnaires and literature study. The results of the research show that the relationship of ad impressions in cinema Anak Langit has a strong relationship with knowledge of Vocational High School 2 Karawangstudents towards Pop Mie Pedes Dower product with value (rs = 0,674). Knowledge of the product is influenced by ad impressions in soap operas that include thoughts about advertising messages, thoughts about the source of advertising, and thoughts about advertising. Keywords: Impressions, Product Knowledge, Advertising Messages, Advertising Source, Advertising